Transcriptome and metabolome analysis of intersex gonads of redclaw crayfish (Cherax quadricarinatus) - He, Ruiqi; Nong, Chuntai; Chen, Yibin; Li, Sedong; Chen, Huapu (Frontiers in Marine Science, 2024)
The redclaw crayfish is sexually dimorphic, with males preferring females in terms of growth rate and size. Currently, the molecular mechanism of sexual dimorphism is not well understood in crustaceans, and studies on the joint analysis of the gonadal metabolome and transcriptome of male and female individuals of redclaw crayfish are limited. In this study, we found that there were differences in relevant metabolites and metabolic pathways between intersex and normal individuals, including metabolites such as testosterone glucuronide, cortisol, pregnenolone sulfate, and estrone glucuronide, as well as steroid hormone synthesis pathways, lipid metabolism pathways, amino acid metabolism and other metabolic pathways. The joint analysis of metabolome and transcriptome identified differential genes such as cyp3a40, cyp18a1, hsd17b12b, and cyp19a, and co-enriched pathways such as insulin signaling pathway, TGF-β signaling pathway, and FoxO signaling pathway, indicating that they may play a significant role in sex differentiation of redclaw crayfish. Our results provide a reference for the molecular mechanism of gonadal development between male and female individuals of redclaw crayfish.